2004
DOI: 10.1124/dmd.104.001891
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Inhibition and Tetrahydrobiopterin Depletion of Endothelial Nitric-Oxide Synthase Caused by Cigarettes

Abstract: ABSTRACT:Smoking causes a dysfunction in endothelial nitric-oxide synthase (eNOS), which is ameliorated, in part, by administration of tetrahydrobiopterin (BH 4 ). The exact mechanism by which the nitric oxide deficit occurs is unknown. We have previously shown that aqueous extracts of chemicals in cigarettes (CE) cause the suicide inactivation of neuronal NO synthase (nNOS) by interacting at the substrate-binding site. In the current study, we have found that CE directly inactivates eNOS by a process that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 27 publications
0
23
0
1
Order By: Relevance
“…[30][31][32] Interestingly, BH 4 is believed to be deficient in conditions associated with altered endothelial function, 30 such as hypercholesterolemia, 33 diabetes, 34 high blood pressure 35 and cigarette smoking. 36,37 Both NO and O 2 À are radicals. These molecules react rapidly with each other to generate peroxynitrite, ONOO À38 (Figure 2), which is an important lipid peroxidation mediator.…”
Section: Endothelial Dysfunction and Oxidative Stress In The Etiologymentioning
confidence: 99%
“…[30][31][32] Interestingly, BH 4 is believed to be deficient in conditions associated with altered endothelial function, 30 such as hypercholesterolemia, 33 diabetes, 34 high blood pressure 35 and cigarette smoking. 36,37 Both NO and O 2 À are radicals. These molecules react rapidly with each other to generate peroxynitrite, ONOO À38 (Figure 2), which is an important lipid peroxidation mediator.…”
Section: Endothelial Dysfunction and Oxidative Stress In The Etiologymentioning
confidence: 99%
“…7 In addition, O 2 Ϫ may interact with NO, leading to the formation of peroxinitrite, further decreasing NO bioavailability. 8,9 eNOS uncoupling, has been demonstrated to modulate endothelial dysfunction in other vascular disorders such as atherosclerosis, 10 diabetes, 11,12 hypertension, 13 hypercholesterolemia, 14 or smoking, 15 and supplementa-tion with BH 4 was able to reverse the reduced NO bioavailability and enhanced O 2 Ϫ production. 14,[16][17][18] This study investigates whether BH 4 deficiency and the ensuing eNOS uncoupling are involved in the reduced NO bioavailability and in the endothelial dysfunction of livers with cirrhosis.…”
mentioning
confidence: 99%
“…Secondly, we anticipated that AP in normal mice would lead to BH 4 oxidation and endothelial dysfunction. Surprisingly, we found that mice with AP had a 5-fold increase over baseline in pancreatic tissue BH 4 concentrations (quantitated by an HPLC fluorescence method [9] ) and a …”
Section: Nos In Experimental Pancreatitis and Associated Pathophysiologymentioning
confidence: 99%
“…Antioxidant effects of BH 4 do not explain these observations because a chemically related pteridine family member, tetrahydroneopterin, has antioxidant properties but no effect on the vasodilatory response in smokers because it cannot couple eNOS to NO synthesis. Recent in vitro studies aimed at chemically identifying the NOS inactivator(s) in cigarettes and cigarette smoke showed that extract prepared from cigarette smoke or unsmoked, ground cigarettes (but not nicotine) irreversibly inhibited nNOS activity by suicide inactivation and reversibly inhibited eNOS enzyme activity by depleting BH 4 within 30-60 min, but nicotine had no effect [9] . Relevant to the pancreas, nNOS inactivation may disrupt neural-mediated smooth muscle relaxation of gastrointestinal tract sphincter muscles, including the sphincter of Oddi, and pose a risk for pancreatitis after endoscopic retrograde cholangiopancreatography (ERCP).…”
Section: Epidemiological Factors Associated With Pancreatic Pathologymentioning
confidence: 99%
See 1 more Smart Citation